Каламуш аорта силлиқ мускул ҲужайраСИ қисқаришига F-37 ва N-24 алкалоидларининг РЕЛАКСАНТ ТАЪСИРини ЎРГАНИШ - Жўрақулов, Ш.Н. (SCIENCE and SOCIETY, 2020)
In the work the effect of alkaloids F-37 and N-24 on the functional activity of the rat aorta smooth muscle cells has been investigated. Contractile activity of rat aortic smooth muscle, precontracted with high phenylephrine, was evaluated by mechanographic technique using isometric force transducer FT–03 (Grass–Telefactor, USA). Results show that alkaloids F-37 (5-100 mkM ) and N-24 (5-200 mkM) induced concentration-dependent relaxation (IC50=25.7 мкМ and IC50=46.6 мкМ, n = 7) of rat aortic rings. These alkaloids also significantly have reduced the contractions of aortic rings induced by phenylephrine and caffeine in Ca2+-free medium. In conclusion we can say that alkaloids F-37 and N-24 possess potent relaxant effect which is related to inhibition of Ca2+ transport through multiple Ca2+ pathways, including receptor–operated Ca2+–channels, as well as, Ca2+ release from sarcoplasmic reticulum.
Keywords: aorta; sarcoplasmic reticulum; alkaloid; Ca2+ channel; caffeine